AN EVALUATION OF ALTERNATİVE METHODS FOR FINANCIAL PERFORMANCE: EVIDENCE FROM TURKEY (ISTANBUL STOCK EXCHANGE) - TEPELI, Yusuf; Özkoç, Hatice (International Journal of Contemporary Economics and Administrative Sciences, 2020)
This study aims to determine which financial performance ranking methods accurately predict the actual rankings by using multiple criteria decision techniques, and it compares the accuracy of the rankings based on the financial performance indicators and the market based approach which involves market value and average return. Companies listed in BIST50 index (Borsa Istanbul) were investigated, as a result, when considering average return, Promethee and Copras produced similar and consistent rankings. Besides, since it places emphasize on the functional structures of variables, Promethee method was noted to produce the most accurate rankings, thus deemed most effective method helping investors give rational decisions.